Hijacked brains : the experience and science of chronic addiction - Barnes, Henrietta N. (Hanover, New Hampshire : Dartmouth College Press, 2015)
"This book, written from the perspective of a practicing primary care physician, interweaves patients' stories with fascinating new brain research to show how addictive drugs overtake basic brain functions and transform them to create a chronic illness that is very difficult to treat. The idea that drug and alcohol addiction are chronic illnesses and not character flaws is not news--this notion has been around for many years. What Hijacked Brains offers is context and personal stories that demonstrate this point in a very accessible package. Dr. Barnes explores how the healthy brain works, how addictive drugs flood basic reward pathways, and what it feels like to grapple with addiction. She discusses how, for individuals, the combination of genetic and environmental factors determines both vulnerability for addiction and the resilience necessary for recovery. Finally, she shows how American culture, with its emphasis on freewill and individualism, tends to blame the addict for bad choices and personal weakness, thereby impeding political and/or health-related efforts to get the addict what she needs to recover." -- Publisher's description.
Learning to use -- Science of addiction -- The sting of stigma -- Risk and resilience -- Recovery : owning the treatment and the outcomes -- Drugs for drugs.
Includes bibliographical references (pages 185-202) and index.
Keywords: Substance abuse -- Psychological aspects; Chronic diseases -- Psychological aspects